Long Non-coding RNA ITIH4-AS1 Accelerates the Proliferation and Metastasis of Colorectal Cancer by Activating JAK/STAT3 Signaling - Chaojie Liang; Tuanjie Zhao; Haijun Li; Fucheng He; Xin Zhao; Yuan Zhang; Xi Chu; Chunlan Hua; Yunhui Qu; Yu Duan; Liang Ming; Jiansheng Guo (Elsevier, 2019)
Accumulating evidence has uncovered long non-coding RNAs (lncRNAs) as central regulators in the pathogenesis of diverse human cancers including colorectal cancer (CRC). The present study discovered that a novel lncRNA ITIH4 antisense RNA 1 (ITHI4-AS1) was frequently under-expressed in most normal human tissues, including colon tissues. Therefore, we aimed to investigate the role of ITHI4-AS1 in CRC. Interestingly, a significant overexpression of ITIH4-AS1 was observed in CRC cell lines relative to normal NCM460 cells. Also, we investigated the facilitating role of ITIH4-AS1 in CRC cell growth and metastasis both in vitro and in vivo. Additionally, we explained that ITIH4-AS1 upregulation in CRC was attributed to downregulation or even depletion of RE1 silencing transcription factor (REST), a presently identified transcriptional repressor for ITIH4-AS1. Meanwhile, the contribution of ITIH4-AS1 to CRC development was validated to rely on the activation of the JAK/STAT3 pathway. More importantly, we verified that FUS interacted with both ITIH4-AS1 and STAT3, and that ITIH4-AS1 evoked nuclear translocation of phosphorylated (p)-STAT3 in CRC through recruiting FUS. In summary, our findings unveiled for the first time that REST downregulation-enhanced ITIH4-AS1 exerts pro-tumor functions in CRC through FUS-dependent activation of the JAK/STAT3 pathway, implying that targeting ITIH4-AS1 may be a novel effective strategy for CRC therapy. Keywords: ITIH4-AS1, colorectal cancer, REST, FUS, STAT3